THE ROLE OF (IT) GOVERNANCE FRAMEWORK'S DIMENSIONS IN LIMITING THE RISKS OF (CAIS): APPLIED TO INDUSTRIAL FIRMS IN IRAQ (World Bulletin of Social Sciences, 2023)
This research seeks to determine the dimensions of (ITG) that could reduce CAIS risks in Iraq industrial firms. This research used a snowball sample technique to collect data from 291 employees worked in Iraq industrial firms. The results showed that all dimensions of (ITG) (Firm & Planning, Acquire & Implementation, Delivery & Support, Monitoring & Evaluation, Guidance & Control) have an impact on the decrease of CAIS risks significantly and positively